2018
DOI: 10.1096/fj.201801511r
|View full text |Cite
|
Sign up to set email alerts
|

Myoglianin triggers the premetamorphosis stage in hemimetabolan insects

Abstract: Insect metamorphosis is triggered by a decrease in juvenile hormone (JH) in the final juvenile instar. What induces this decrease is therefore a relevant question. Working with the cockroach Blattella germanica, we found that myoglianin (Myo), a ligand in the TGF‐β signaling pathway, is highly expressed in the corpora allata (CA, the JH‐producing glands) and the prothoracic gland [(PG), which produce ecdysone] during the penultimate (fifth) nymphal instar (N5). In the CA, high Myo levels during N5 repress the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…While the clearance of JH is necessary to initiate metamorphosis, 417 the threshold size assessment must occur earlier. Myo has been shown to act upstream of JH 418 signaling in hemimetabolous insects: myo knockdown leads to an increase in jhamt expression in 419 the corpora cardiaca/corpora allata (Kamsoi and Belles, 2019). Thus, Myo is likely the threshold 420 size determinant that ultimately causes a drop in JH titer.…”
Section: Jh Does Not Affect Threshold Size Of M Sexta 408mentioning
confidence: 99%
See 4 more Smart Citations
“…While the clearance of JH is necessary to initiate metamorphosis, 417 the threshold size assessment must occur earlier. Myo has been shown to act upstream of JH 418 signaling in hemimetabolous insects: myo knockdown leads to an increase in jhamt expression in 419 the corpora cardiaca/corpora allata (Kamsoi and Belles, 2019). Thus, Myo is likely the threshold 420 size determinant that ultimately causes a drop in JH titer.…”
Section: Jh Does Not Affect Threshold Size Of M Sexta 408mentioning
confidence: 99%
“…Knockdown of Kr-h1 in the penultimate nymphal instar of the 111 firebug, Pyrrhocoris apterus, the German cockroach, Blattella germanica, and the brown 112 planthopper, Nilaparvata lugens, leads to precocious adult development (Konopova et al, 2011;113 Li et al, 2018;Lozano and Belles, 2011). In addition, silencing myoglianin (myo), a gene coding 114 for one of the ligands of the TGF-beta/Activin signaling pathway, has been shown to cause extra 115 nymphal molts (Ishimaru et al, 2016;Kamsoi and Belles, 2019): Increased expression of myo 116 has been shown to trigger the final nymphal instar in Blattella germanica (Kamsoi and Belles, 117 2019). Myo expression in the corpora allata/corpora cardiaca in the fifth (penultimate nymphal) 118 instar nymphs leads to the repression of the JH biosynthesis gene, jhamt, in the sixth (last) instar 119 nymphs (Kamsoi and Belles, 2019).…”
mentioning
confidence: 99%
See 3 more Smart Citations